Perngaruh Kualitas Sistem dan Kualitas Layanan Terhadap Kepuasan Pengguna E-Learning - Khairani Dwi Hadrina Pohan; Rose Rahmidani (Jurnal Ecogen, 2021)
The purpose of researche is to know the role of System Quality and Service Quality on User Satisfation student Padang State University. This research used quantitative descriptive method, the population in this research were students Padang State University.Number of samples were decided base on hair et. As many as 100 people and were chosen by using proportional stratified Random Sampling. Data were used is primer data were provided through questionnaire shared to students Padang State University based on predetermined criteria. Analysis method was used is multiple regression by using spss 20. The result of this research shows (1) System Quality have significant affect on User Satisfaction, (2) Service Quality  have significant effect on User Satisfaction.